Diving accidents treated at a military hospital-based recompression chamber facility in Peninsular Malaysia. - Ahmad, Rozali; Khairuddin, H.; Mohd Sidik, Sherina; M., Abd Halim; B., Mohd Zin; Sulaiman, Abdul Hadi (Malaysian Medical Association, 2008)
This paper describes the pattern of diving accidents treated in a military hospital-based recompression chamber facility in Peninsular Malaysia. A retrospective study was carried out to utilize secondary data from the respective hospital medical records from 1st January 1996 to 31st December 2004. A total of 179 cases categorized as diving accidents received treatment with an average of 20 cases per year. Out of 179 cases, 96.3% (n=173) received recompression treatment. Majority were males (93.3%), civilians (87.2%) and non-Malaysian citizens (59.2%). Commercial diving activities contributed the highest percentage of diving accidents (48.0%), followed by recreational (39.2%) and military (12.8%). Diving accidents due to commercial diving (n=86) were mainly contributed by underwater logging activities (87.2%). The most common cases sustained were decompression illness (DCI) (96.1%). Underwater logging and recreational diving activities which contribute to a significant number of diving accidents must be closely monitored. Notification, centralised data registration, medical surveillance as well as legislations related to diving activities in Malaysia are essential to ensure adequate monitoring of diving accidents in the future.